2022
DOI: 10.5114/biolsport.2021.101128
|View full text |Cite
|
Sign up to set email alerts
|

Drop jumps improve repeated sprint ability performances in professional basketball players

Abstract: To verify the acute effect of drop jumps (DJ) on two repeated sprint ability tests (RSA), interspersed with a rest period simulating a basketball game break. Twelve first division basketball players (age: 24.8 ± 6.9 years; body mass: 97.0 ± 9.2 kg; height: 2.0 ± 0.1 m) performed, in a randomized crossover design, two RSA tests separated by 5 min after DJ or control conditions. The DJ condition comprised 5 DJs performed 4 min prior to the first RSA test, whereas 3 DJ were completed 30 s prior to a second RSA te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 28 publications
(42 reference statements)
2
19
0
Order By: Relevance
“…rectus femoris, vastus lateralis, vastus medialis and gluteus maximus). These recent results are in agreement with another recent study by Zagatto et al [1], who measured the EMG signal during RSA sprints after drop jumps in professional basketball players but without changes in EMG Fig. 3 EMG activity of selected lower-limb muscles measured during repeat-sprint ability test, normalized by the first sprint values observed in control condition (n = 10).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…rectus femoris, vastus lateralis, vastus medialis and gluteus maximus). These recent results are in agreement with another recent study by Zagatto et al [1], who measured the EMG signal during RSA sprints after drop jumps in professional basketball players but without changes in EMG Fig. 3 EMG activity of selected lower-limb muscles measured during repeat-sprint ability test, normalized by the first sprint values observed in control condition (n = 10).…”
Section: Discussionsupporting
confidence: 91%
“…A previous study has reported a correlation between RSA mean time, and distance covered during high intensity actions throughout matches [28]. In a recent study, Zagatto et al [1] investigated the PAPE effects of drop jumps (1 × 5 drop jumps before a first RSA testing, and 1 × 3 drop jumps before a second RSA) in professional basketball players, and also found a greater best time, total time, and mean time in both RSA tests after the drop jumps condition, thus corroborating the current findings. In the present study, a greater mean time, total time, and reduction on the slowest time after drop jumps was found.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations